The phytoestrogens daidzein and equol inhibit the drug transporter BCRP/ABCG2 in breast cancer cells: potential chemosensitizing effect - Rigalli, Juan Pablo; Scholz, Paul Niklas; Tocchetti, Guillermo Nicolás; Weiß, Johanna (European journal of nutrition, 2019)
Purpose: The soy isoflavone genistein has been described to up-regulate breast cancer resistance protein (BCRP) and, thus, enhance chemoresistance in breast cancer cells. The aim of this work was to assess the effect of long- and short-term incubation with daidzein, the second most abundant soy isoflavone and its metabolite equol on the expression and activity of P-glycoprotein, multidrug resistance-associated proteins 1 and 2 (MRP1 and MRP2) and BCRP in breast cancer cells. Methods: MCF-7 and MDA-MB-231 cells were treated with phytoestrogen concentrations within the range achieved in individuals with a high isoflavone intake. Transporter expression was evaluated at protein and mRNA level through western blot and qRT-PCR, respectively. Transporter activity was determined using doxorubicin, mitoxantrone and carboxy-dichlorofluorescein as substrates. Results: Daidzein (5 µM) up-regulated MRP2- and down-regulated MRP1 protein expressions in MCF-7 and MDA-MB-231 cells, respectively. Both effects were ER-dependent, as determined using the antagonist ICI 182,780. The decrease in MRP1 mRNA in MDA-MB-231 cells indicates a transcriptional mechanism. On the contrary, MRP2 induction in MCF-7 cells takes place post-transcriptionally. Whereas changes in the transporter expression had a minor effect on the transporter activity, acute incubation with daidzein, R-equol and S-equol led to a strong inhibition of BCRP activity and an increase in the IC50 of BCRP substrates. Conclusions: In contrast to previous reports for genistein, daidzein and equol do not provoke a major up-regulation of the transporter expression but instead an inhibition of BCRP activity and sensitization to BCRP substrates.
First online: 03 November 2017
Gesehen am 26.06.2018